Peran Penyidik Pegawai Negeri Sipil (PPNS) Terhadap Penegakan Hukum Kekayaan Intelektual Di Kantor Wilayah Kementerian Hukam Dan Ham Sumatera Utara - Lubis, Muhammad Koginta; Ramadhan, M. Citra; Isnaini, Isnaini (Mahesa Research Center, 2023)
The purpose of this paper is to analyze the legal arrangements regarding the role of Civil Servant Investigators (PPNS) in enforcing intellectual property and what factors influence it in the office of the Ministry of Law and Human Rights of North Sumatra. The research method used is normative-empirical legal research, in order to obtain normative legal provisions and their application to any particular legal event. The results of the study show that the role of Civil Servant Investigators (PPNS) in enforcing intellectual property law is contained in article 1 paragraph (1) of Law Number 8 of 1981 concerning criminal procedure law (KUHAP) and in Laws related to Intellectual Property, apart from it is specifically regulated in Kepmenkumham Number M.HH-01-.H1.07.02 of 2015 concerning Guidelines for Implementation of Crime Management in the Field of Intellectual Property including: pre-emptive, preventive and repressive roles; In carrying out its role as a law enforcer for criminal acts of intellectual property rights it has not been maximized; and Factors that influence law enforcement on criminal acts of intellectual property rights, namely: statutory factors, in the matter of complaint offenses; law enforcement factors, in the case of a minimum number of members; Facility and infrastructure factors that are less supportive; factor of legal awareness, in terms of the lack of legal counseling; and cultural factors, related to differences in norms in intellectual property law between those in society and regulations.